2016
DOI: 10.1039/c5dt04975j
|View full text |Cite
|
Sign up to set email alerts
|

A morphology, porosity and surface conductive layer optimized MnCo2O4 microsphere for compatible superior Li+ ion/air rechargeable battery electrode materials

Abstract: Uniform surface conductive layers with porous morphology-conserved MnCo2O4 microspheres are successfully synthesized, and their electrochemical performances are thoroughly investigated. It is found that the microwave-assisted hydrothermally grown MnCo2O4 using citric acid as the carbon source shows a maximum Li(+) ion lithiation/delithiation capacity of 501 mA h g(-1) at 500 mA g(-1) with stable capacity retention. Besides, the given microsphere compounds are effectively activated as air cathode catalysts in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Figure a and b shows the first 5 CV curves of the MCO and NMCO samples, respectively in the potential window of 0–3.0 V at a scan rate of 0.5 mV s −1 . For MCO, in the first cathodic sweep (Figure a), a broad peak appears at 1.2 and sharp reduction peak at 0.8 V, corresponding to the decomposition and reduction of MnCo 2 O 4 to metallic manganese and cobalt, the electrochemical formation of amorphous Li 2 O and a passivating SEI film . During the subsequent anodic scan, two peaks are located at 1.65 V and 2.05 V, which are ascribed to the oxidation of Mn to Mn 2+ and Co to Co 2+ .…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Figure a and b shows the first 5 CV curves of the MCO and NMCO samples, respectively in the potential window of 0–3.0 V at a scan rate of 0.5 mV s −1 . For MCO, in the first cathodic sweep (Figure a), a broad peak appears at 1.2 and sharp reduction peak at 0.8 V, corresponding to the decomposition and reduction of MnCo 2 O 4 to metallic manganese and cobalt, the electrochemical formation of amorphous Li 2 O and a passivating SEI film . During the subsequent anodic scan, two peaks are located at 1.65 V and 2.05 V, which are ascribed to the oxidation of Mn to Mn 2+ and Co to Co 2+ .…”
Section: Resultsmentioning
confidence: 60%
“…However, the NMCO nanowire electrode reveals admirable cyclability of 98 % specific capacity retention over 200 cycles. Significantly, among both samples, the NMCO sample confer the utmost reversible capacity and much better than earlier reports . It reveals the good stability ofstructure and good electrochemical Li + insertion/extraction.…”
Section: Resultsmentioning
confidence: 99%
“…The need for free‐standing carbon‐free electrodes for LOB encouraged the exploration of materials, previously used as catalysts . Several approaches have been proposed to narrow the gap toward a feasible LOB, namely metals and/or transition metal compounds (TMC – oxides, carbides, and nitrides).…”
Section: Toward Carbon‐free Air Electrodesmentioning
confidence: 99%
“…While porous structure can alleviate oxygen and Li + diffusion and increase the active surface area for ORR, low electronic conductivity and poor diffusion of active species lead to poor rate capabilities. The last has been often alleviated in LOBs by additional conductive substrates, special nano‐scale architectures (microspheres, nanoparticles, web‐like, nanowires, scale‐ and rod‐like, nanorods, etc.) of binary metal oxides, and surface alterations .…”
Section: Toward Carbon‐free Air Electrodesmentioning
confidence: 99%
“…Moreover, Kim et al also reported that MnCo 2 O 4 nanowires anchored on rGO nanosheets could significantly improve the discharge specific capacity, rate capability, and cycle life when they were severed as cathodic materials for Li–O 2 battery . More recently, carbon layer coated MnCo 2 O 4 multiporous microspheres were prepared by a simple co‐preciptation and subsequent hydrothermal method, and this hybrid promoted the electrochemical reaction of the oxygen cathode and achieved a remarkable cyclic stability.…”
Section: Manganese‐based Composite Oxidesmentioning
confidence: 99%